The Effect of Good Governance Practices and Decision Making at Da’wah and Communication Faculty UIN Raden Fatah Palembang - M. Ed, Manalullaili (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Raden Fatah Palembang, 2023)
In the dynamic landscape of higher education, effective governance practices and decision-making within academic institutions are pivotal for shaping the academic environment. This holds particularly true for faculties dedicated to Da'wah and Communication, where religious principles, communication, and academic rigor converge. This study explores governance practices and decision-making dynamics within the Da’wah and Communication Faculty at UIN Raden Fatah Palembang. The research delves into administrative structures, decision-making processes, and their impact on academic, religious, and communicative dimensions. Differentiating educational governance from corporate governance, the study underscores the complexity of educational contexts. In the Da’wah and Communication Faculty, the Management Review Meeting serves as a crucial governance practice. The meeting involves agenda overview, prior meeting evaluation, academic contributions, student affairs, financial analysis, technology assessment, and open discussion. This strategic approach enhances organizational performance, aligning with the principles of good governance. The research methodology employs a quantitative approach, utilizing cross-sectional data from interviews and questionnaires. The Likert scale measures perceptions, with decision-making as the dependent variable and good governance as the independent variable. Hypothesis testing involves simple linear regression and partial tests. Research findings suggest a positive but statistically insignificant correlation between knowledge management (KM) and decision making (DM). Influencing factors include small sample sizes, high variability, insensitive measurement methods, unaccounted control variables, temporal aspects, and chance factors. Enhancing significance requires expanded sample sizes, detailed control variables, and robust statistical methods. Contextual considerations are crucial, emphasizing the context-dependent nature of the KM-DM relationship. In conclusion, the KM-DM relationship is generally perceived as positive, yet lacks consistent statistical significance. Factors influencing this relationship necessitate methodological improvements. Recognizing the context-dependent nature of KM's impact on decision-making outcomes, researchers can refine strategies for more targeted decision-making in educational organizations.